Sri Lankan weevil Myllocerus undecimpustulatus undatus Marshall - Anita Neal (EDIS)
Myllocerus undecimpustulatus undatus Marshall, the Sri Lankan weevil, is a plant pest with a wide range of hosts. This weevil spread from Sri Lanka into India and then Pakistan where many subspecies of Myllocerus undecimpustulatus Faust are considered pests of more than 20 crops. In the United States, the Sri Lankan weevil was first identified on Citrus sp. in Pompano Beach a city in Broward County Florida. Three specimens were identified by Dr. Charles W. O’Brien, first as Myllocerus undecimpustulatus, a species native to southern India, and then again as Myllocerus undatus Marshall native to Sri Lanka, finally as Myllocerus undecimpustulatus undatus Marshall to show its status as a subspecies. This 4-page fact sheet was written by Anita Neal, and published by the UF Department of Entomology and Nematology, November 2013. http://edis.ifas.ufl.edu/in1016